Identification of alkaloids and related intermediates of Dendrobium officinale by solid-phase extraction coupled with high-performance liquid chromatography tandem mass spectrometry - Song, Cheng; Zhang, Yunpeng; Manzoor, Muhammad Aamir; Li, Guohui (Frontiers in Plant Science, 2022)
Jasmonate (JA) signaling plays a pivotal role in plant stress responses and secondary metabolism. Many studies have demonstrated that JA effectively induce the expressions of alkaloid biosynthetic genes in various plants, which rendered to the accumulation of alkaloid to counteract stresses. Despite the multiple roles of JA in the regulation of plant growth and different stresses, less studied involved in the regulatory role of JA in D. officinale alkaloids. A strategy for the rapid identification of alkaloid and the intermediates of D. officinale was established based on a solid-phase extraction coupled with high-performance liquid chromatography tandem mass spectrometry method. By using SPE-LC-MS/MS method, the potential compounds were tentatively identified by aligning the accurate molecular weight with the METLIN and Dictionary of Natural Products databases. The chemical structures and main characteristic fragments of the potential compounds were further confirmed by retrieving the multistage mass spectra from the MassBank and METLIN databases.The Mass Frontier software was used to speculate the fragmentation pathway of the identified compounds. Seven alkaloids were separated and identified from D. officinale, which were mainly classified into five types (tropane alkaloids, tetrahydroisoquinoline alkaloids, quinolizidine alkaloids, piperidine alkaloids and spermidine alkaloids). Besides the alkaloids, forty-nine chemical substances, including guanidines, nucleotides, dipeptides, sphingolipids and nitrogen-containing glucosides, were concurrently identified. These findings gives the composition of chemicals currently found in D. officinale, which could provide the scientific method for the identification of alkaloids in other Dendrobium plants.